2019
DOI: 10.1177/1558925019886407
|View full text |Cite
|
Sign up to set email alerts
|

Inspection for supercritical CO2 dyeing of poly(m-phenylene isophthalamide) by kinetics and thermodynamics analysis

Abstract: Eco-friendly dyeing by using supercritical carbon dioxide as a medium has already been investigated worldwide due to the advantages of dyeing without water and recyclability of dyes and carbon dioxide. In this article, dyeing mechanism of poly(m-phenylene isophthalamide) was investigated in supercritical carbon dioxide. The obtained results showed that the dye uptake of Disperse Red 60 increased moderately with the temperature raising at constant pressure and achieved dyeing equilibrium after 70 min. By adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Between the two major types of aramids of meta‐aramids and para‐aramids, the meta‐aramid fibers consist of poly(m‐phenylene isophthalamide) that bind via meta‐linked aromatic rings to result in a semi‐crystalline fiber with the molecular chain oriented along the fiber axis, while the building‐blocks of para‐aramids are poly(p‐phenylene terephthalamide) with stiff para‐linked aromatic rings and densely arranged hydrogen bond donors and acceptors throughout their backbones (Roenbeck et al, 2019). Our literature searches on ScCO 2 dyeing of aramids found that (1) most studies claimed successful dyeing of meta‐aramids, but few of para‐aramids; (2) most studies used disperse dyes because they are soluble in ScCO 2 ; and (3) most studies relied on the addition of auxiliary chemicals, such as dimethyl terephthalate, ethyl alcohol, or CINDYE DNK as carriers, to enhance dyeing performance (Ye et al, 2019; Zheng et al, 2017; Zheng & Zheng, 2014). It is more difficult to dye para‐aramids than meta‐aramids, because the inherent molecular rigidity of para‐aramids, combined with strong intermolecular hydrogen bonding interactions, enables the molecules to achieve excellent alignment with their neighbors, resulting in a highly anisotropic unit cell consisting of covalent bonds, hydrogen bonds, and van der Waals interactions along each fundamental axis, forming a highly crystalline structure (Roenbeck et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Between the two major types of aramids of meta‐aramids and para‐aramids, the meta‐aramid fibers consist of poly(m‐phenylene isophthalamide) that bind via meta‐linked aromatic rings to result in a semi‐crystalline fiber with the molecular chain oriented along the fiber axis, while the building‐blocks of para‐aramids are poly(p‐phenylene terephthalamide) with stiff para‐linked aromatic rings and densely arranged hydrogen bond donors and acceptors throughout their backbones (Roenbeck et al, 2019). Our literature searches on ScCO 2 dyeing of aramids found that (1) most studies claimed successful dyeing of meta‐aramids, but few of para‐aramids; (2) most studies used disperse dyes because they are soluble in ScCO 2 ; and (3) most studies relied on the addition of auxiliary chemicals, such as dimethyl terephthalate, ethyl alcohol, or CINDYE DNK as carriers, to enhance dyeing performance (Ye et al, 2019; Zheng et al, 2017; Zheng & Zheng, 2014). It is more difficult to dye para‐aramids than meta‐aramids, because the inherent molecular rigidity of para‐aramids, combined with strong intermolecular hydrogen bonding interactions, enables the molecules to achieve excellent alignment with their neighbors, resulting in a highly anisotropic unit cell consisting of covalent bonds, hydrogen bonds, and van der Waals interactions along each fundamental axis, forming a highly crystalline structure (Roenbeck et al, 2017).…”
Section: Introductionmentioning
confidence: 99%